2013
DOI: 10.3126/jiom.v34i2.9045
|View full text |Cite
|
Sign up to set email alerts
|

Tear Film Evaluation in Contact Lens Wearers and Non Wearers

Abstract: Background: Dry eye symptoms are more frequent in contact lens wearers than in non wearers. Dry eye is considered relatively common in contact lens wearers than non-wearers. However, there was no any report in our clinical setting that compared and addressed the issue related to dry eye and its symptom in contact lens wearers. The present study was conducted to compare pre-ocular tear lm in contact lens wearers (CLW) and contact lens non wearers (CLNW), and evaluate the relationship between clinical and subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Lira et al [ 22 ] found a statistically significant reduction in NIBUT during the day of about 1.2 s in non-CL wearers. In another study [ 42 ], a reduction of 0.1 s was observed in asymptomatic CL wearers and 2.55 s in the symptomatic ones after 5 h of CL wear. Although statistically nonsignificant, the present findings suggest that Delefilcon A lenses may have a lesser impact on the stability of PLTF throughout the day compared to Stenfilcon A lenses.…”
Section: Discussionmentioning
confidence: 96%
“…Lira et al [ 22 ] found a statistically significant reduction in NIBUT during the day of about 1.2 s in non-CL wearers. In another study [ 42 ], a reduction of 0.1 s was observed in asymptomatic CL wearers and 2.55 s in the symptomatic ones after 5 h of CL wear. Although statistically nonsignificant, the present findings suggest that Delefilcon A lenses may have a lesser impact on the stability of PLTF throughout the day compared to Stenfilcon A lenses.…”
Section: Discussionmentioning
confidence: 96%